Robot rebellion - Neal, Rie; Shipman, Talitha (New York : Aladdin, 2023)
Banding together to create the perfect gift for their teacher's big birthday, Astrid and the rest of the Shooting Stars decide to have their robot do a fun dance for her during the robotics competition, but things don't go as planned.
Keywords: After-school programs -- Juvenile fiction; Clubs -- Juvenile fiction; Contests -- Juvenile fiction; Hearing impaired -- Juvenile fiction; Robots -- Juvenile fiction; School fiction